Animal Rescue Friends. 2, Friends fur-ever - Tropper, Jana; Kote, Genevieve; Trinidad, Leo; Hashimoto, Meika; Loveless, Gina (Kansas City, Missouri : Andrews McMeel Publishing, 2022)
It's the start of a new school year, and the kids are excited about their new club, Oakville Elementary School's Club for Animal Appreciation, Education, and Rehabilitation--even if their new club advisor, Mrs. Wen, doesn't share their enthusiasm. But as they meet a decidedly unusual crew of animals, including a bearded dragon who won't eat, a therapy pig named Truffles, and a prickly porcupine who needs first aid, the kids and adults alike learn that when people help animals, the animals help them right back.
Animal Rescue Friends created by Meika Hashimoto, Gina Loveless, and Genevieve Kote.
3.9
3-6
GN520L
Keywords: Animal rescue -- Comic books, strips, etc; Animal rescue -- Juvenile fiction; Pets -- Comic books, strips, etc; Pets -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Elementary schools -- Comic books, strips, etc; Elementary schools -- Juvenile fiction; Clubs -- Comic books, strips, etc; Clubs -- Juvenile fiction; Animal rescue -- Fiction; Pets -- Fiction; Friendship -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Clubs -- Fiction; School comics; Animal fiction; Graphic novels; Comics (Graphic works)